Angelica sinensis Improves Exercise Performance and Protects against Physical Fatigue in Trained Mice - Yeh, Tzu-Shao (Molecules, 2014)
Angelica sinensis (AS) is a well-known medicinal herb and food material with antioxidative and multifunctional pharmacological activities. However, we lack evidence of the effect of AS on exercise performance and physical fatigue. We aimed to evaluate the potential beneficial effect of AS on ergogenic and anti-fatigue functions after physiological challenge. Male ICR strain mice were randomly assigned to four groups (n = 10 per group) for treatment: (1) sedentary control and vehicle treatment (vehicle control); (2) exercise training with vehicle treatment (exercise control); (3) exercise training with AS treatment at 0.41 g/kg/day (Ex-AS1); and (4) 2.05 g/kg/day (Ex-AS5); both the vehicle and AS were orally administered for 6 weeks. Exercise performance and anti-fatigue function were evaluated by forelimb grip strength, exhaustive swimming time, and levels of serum lactate, ammonia, glucose, and creatine kinase (CK) after a 15-min swimming exercise. Trend analysis revealed that AS treatments significantly increased endurance swimming time and blood glucose level, and decreased serum lactate, ammonia and CK levels. Liver and muscle glycogen contents were higher for Ex-AS1 and Ex-AS5 groups than the exercise control. Therefore, AS supplementation improved exercise performance and had anti-fatigue properties in mice and may be an effective ergogenic aid in exercise training.